The Emergence of Natural Killer Cells as a Major Target in Cancer Immunotherapy. Issue 2 (February 2019) - Souza-Fonseca-Guimaraes, Fernando; Cursons, Joseph; Huntington, Nicholas D.
Abstract : Immune 'checkpoint' inhibitors can increase the activity of tumor-resident cytotoxic lymphocytes and have revolutionized cancer treatment. Current therapies block inhibitory pathways in tumor-infiltrating CD8 + T cells and recent studies have shown similar programs in other effector populations such as natural killer (NK) cells. NK cells are critical for immunosurveillance, particularly the control of metastatic cells or hematological cancers. However, how NK cells specifically recognize transformed cells and dominant negative feedback pathways, as well as how tumors escape NK cell control, remains undefined. This review summarizes recent advances that have illuminated inhibitory checkpoints in NK cells, some of which are shared with conventional cytotoxic T lymphocytes. It also outlines emerging approaches aimed at unleashing the potential of NK cells in immunotherapy. Highlights: NK cells possess the innate ability to detect transformed cells, and thus, are key to cancer immunosurveillance and antitumor immunity, particularly in hematological cancers and the control of metastatic dissemination. Immune checkpoint inhibitors that function by enhancing cytotoxic immune responses of tumor-infiltrating lymphocytes have revolutionized the cancer therapy landscape. Seminal discoveries in NK cell biology have culminated in recent breakthroughs with the identification of potent 'checkpoints' for NK cell activation, several of which may be shared with T cells. Given the ability of NK cells to detect and destroy a range of cancerous tissues, mechanistic insight into how cancer cells regulate NK cell checkpoints and the pharmacological modulation of these checkpoints represents an unmet need for immunotherapy development.